2011
DOI: 10.1021/jp201062m
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility and High Storage Capacity of Lithium in sp–sp2 Hybridized Carbon Network: The Case of Graphyne

Abstract: We have carried out first-principles calculations to explore the energetics and dynamics of Li in graphyne, a novel carbon allotrope consisting of spÀsp 2 hybridized carbon atoms, relevant for anode lithium intercalation in rechargeable Li-ion batteries. In contrast to graphite where Li diffusion is confined in the interlayer space (in-plane diffusion), the unique atomic arrangement and electronic structures enable both inplane and out-plane diffusion of Li ions in graphyne with moderate barriers, 0.53À0.57 eV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
171
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(185 citation statements)
references
References 45 publications
(80 reference statements)
12
171
2
Order By: Relevance
“…1, was considered to simulate the substrate. The optimized lattice constant is 9.7 Å, in good agreement with other DFT calculations [33][34][35] . Due to the diversity in the hybridization of the carbon-carbon bonds in the −C≡C−C≡C− chains in graphdiyne, the bond lengths along the chain are different: 1.39, 1.23, 1.33, 1.23, and 1.39 Å, aligned from one carbon hexagon to the nearest carbon of an adjacent hexagon.…”
Section: Methodssupporting
confidence: 87%
“…1, was considered to simulate the substrate. The optimized lattice constant is 9.7 Å, in good agreement with other DFT calculations [33][34][35] . Due to the diversity in the hybridization of the carbon-carbon bonds in the −C≡C−C≡C− chains in graphdiyne, the bond lengths along the chain are different: 1.39, 1.23, 1.33, 1.23, and 1.39 Å, aligned from one carbon hexagon to the nearest carbon of an adjacent hexagon.…”
Section: Methodssupporting
confidence: 87%
“…They are considered as possible promising materials for nanoelectronics, for hydrogen storage, as membranes (for example, for hydrogen separation from syngas -as an alternative for nanomeshy graphene), for energy storage applications or as candidates for the anode material in batteries [20][21][22][23][24][25][26]. Thus, the tuning of the properties of these materials should be critical for their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to graphene with identical  bindings, graphyne has three types of  bindings, C(sp 2 )-C(sp 2 ), C(sp)-C(sp 2 ), and C(sp)-C(sp), as shown in Figure 1. A number of theoretical calculations on graphyne monolayer [13,[16][17][18][19] and graphyne-related nanomaterials [20][21][22] have been performed to reveal their unique properties and potential applications. First-principles calculations showed that single-layered graphyne is semiconducting with a small direct band gap of ~0.5 eV at M point [16].…”
mentioning
confidence: 99%